HUBUNGAN KEKERABATAN FENETIK 7 SPESIES JERUK DI DATARAN TINGGI BENER MERIAH - Agustina, Aulia; Hasanuddin, Hasanuddin (Jurnal Jeumpa, 2021)
The study about “Phenetic Relationship of 7 Species of Orange Plants in BenerMeriah Highlands” was inducted back in August until September 2017. The aim of this study is to describe the morphological characterization of 7 species of orange plants in BenerMeriah highlands and to understand the phenetic relationship of 7 species of oranges plant in BenerMeriah highlands. The method used in this study was observation with the type of mixture between qualitative and quantitative. The subjects of this study are 7 species of orange plants, namely: a) Citrus reticulata; b) Citrus amblycarpa; c) Citrus hystrix; d) Citrus nobilis; e) Citrus maxima; f) Citrus sinensis; and g) Citrus aurantifolia. The parameters of this study were the morphological characteristic of stems, leaves, fruits and flowers. The collected data were analyzed descriptively, where the similarities were measured using Similarity Index (SI) and the dissimilarities were measured using Dissimilarity Index (DI) to classify the total of 7 species of orange plants using cluster analysis. According to the morphological characteristics, it could be concluded that there are several differences and similarities among the 7 species of orange plants found in BenerMeriah Regency. The combination of Citrus hystrix with Citrus aurantifolia have the closest phenetic relationship, which have 66 of SI. The other combinations that also have close phenetic relationship are Citrus hystrix with Citrus maxima and Citrus nobilis with Citrus sinensis. The pheneticrelationship that have the highest DI is the combination of Citrus amblycarpa with Citrus maxima, which have 88 of DI